Utilization of palm sludge for biosurfactant production - Jamal, Parveen; Wan Nawawi, Wan Mohd Fazli; Alam, Md. Zahangir (CRC Press (Taylor & Francis), 2015)
Demand for surfactant chemicals for household cleaning products, personal care sectors, agriculture, food, pharmaceutical, and environmental industries is steadily increasing. According to 2013 Acmite Market Intelligence report [1], the world markets of surfactants reached US$26.8 billion in 2012, experiencing 10% increase since 2010. These figures are predicted to increase by 3.8% annually in the coming years and by 2016, the market is expected to reach US$31.1 billion. However, due to the potential hazard of synthetic surfactant toward human health and the increasing consumer demand for chemical product, both effective and environmentally compatible, it is natural to turn to the microbial world to fulfill this demand by means of biosurfactant utilization. Microbial-derived surfactants are produced on living surface, mostly microbial cell surface or excreted extracellularly and contain hydrophilic and hydrophobic moieties capable of reducing surface tension and interfacial tension between individual molecules at the surface and interface. Such properties exhibit excellent detergency, emulsifying, foaming, and dispersing traits, which can be applied in various industries. It is also commercially promising alternatives to chemically synthesized surfactants due to their inherent biodegradability, lower toxicity, better foaming properties, and greater stability toward temperature and pH [2]. However, large-scale production of biosurfactant is still at its infancy due to expensive raw material, low production yield, and high purification cost. Selection of inexpensive and nutrient-rich raw materials is crucial to the economics of the process because they highly influence the overall production cost. Recently, several renewable substrates, especially from oily-based agroindustrial wastes, have been extensively studied for microbial surfactant production as it confers cost-free or low-cost feed stocks [3]. Mercade et al. [4] reported use of olive oil mill effluent for rhamnolipid production by Pseudomonas sp. Soap stick oil has been used for rhamnolipid production with P. aeruginosa [5]. Mulligan and Cooper used water collected during drying of fuel grade peat [6]. Raza et al. [7] evaluate waste frying oil from canola, corn, and soybean as a substrate for rhamnolipid production by Pseudomonas aeruginosa mutant EBN-8. Several studies with water-immiscible raw material such as plant-derived oils and oil wastes have shown that they can act as effective and cheap raw materials for biosurfactant production. Biosurfactant products obtained by using water-soluble carbon sources such as glycerol, glucose, mannitol, and ethanol are reported to be inferior to that obtained with water-immiscible substrate such as n-alkanes and olive oil [8,9]. Banat [10] observed little biosurfactant production when cells were grown on a readily available carbon sources. The production of biosurfactant was triggered only when all the soluble carbon was consumed and when a water-immiscible hydrocarbon was available. Rapeseed oil [11], canola oil, babassu oil, and corn oil [12,13] are plant-derived oils that have been used as raw material for biosurfactant production. Similarly, vegetable oils such as sunflower and soybean oils [14,15] were used for the production of rhamnolipid, sophorolipid, and mannosylerythritol lipid biosurfactants by various microorganisms. Despite ongoing research using unconventional sources, selection of appropriate waste substrate is still a challenge. Researchers are facing the problem of finding a waste with the right balance of carbohydrates and lipids to support optimal growth of microorganisms and maximum production of biosurfactant [16]. Search for new strains for high productivity is also a challenge for the widespread application of microbial surfactants. In addition, process conditions improvement through statistical optimization can be implemented as one of the effective approaches to increase the production yield of biosurfactant. Enhanced product yield, closer conformance or the process output to target requirement and reduced process variability, development time, and cost can be realized by the application of statistical experimental design techniques in bioprocess development and optimization [17]. Therefore, the aim of this chapter is to demonstrate investigation and results on an inexpensive raw material derived from palm oil refinery waste for biosurfactant production by potential isolated strain as well as enhancing the development process through series of optimization studies of nutritional requirement for maximum biosurfactant production. For this, a lab research was conducted by the authors.